2002
DOI: 10.1034/j.1600-0501.2002.130409.x
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus augmentation model in rabbits: effect of occluded nasal ostium on new bone formation

Abstract: This study was undertaken to establish an experimental model for maxillary sinus augmentation in rabbits and to clarify the bone response to the occluded nasal ostium. In rabbits without ostial occlusion, the elevation of the sinus mucosa resulted in formation of a subantral hollow space filled with blood clots and granulation tissue 1 week after operation. The newly formed bone filled in the space had a central granulation tissue. The space was almost completely replaced by a normal sinus airspace after 3 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 15 publications
8
109
0
3
Order By: Relevance
“…Studies on animal models [57][58][59] have demonstrated that sinus augmentations match with the biologic concept of GBR; however, implants are usually placed after approximately 6 months of GBR. In nearly 60 % studies, bone height under the maxillary sinus floor was 4-5 mm, and sinus augmentation protocols were adopted in atrophic posterior maxillae to increase the bone height for future implant placement.…”
Section: Discussionmentioning
confidence: 98%
“…Studies on animal models [57][58][59] have demonstrated that sinus augmentations match with the biologic concept of GBR; however, implants are usually placed after approximately 6 months of GBR. In nearly 60 % studies, bone height under the maxillary sinus floor was 4-5 mm, and sinus augmentation protocols were adopted in atrophic posterior maxillae to increase the bone height for future implant placement.…”
Section: Discussionmentioning
confidence: 98%
“…The rabbits were anaesthetized by intravenous injection of pentobarbital sodium (1.5 mg/kg) dissolved in sterile 0.9% saline, and 0.5 ml of 1% lidocaine with epinephrine (1:100,000) was injected subcutaneously at the midline of the nasal dorsum for local anaesthesia. A 3 cm vertical midline incision was made as described by ASAI et al 1 , and the skin and periosteum were elevated sufficiently to expose the nasal bone and nasoincisal suture line. Two circular nasal bone windows (diameter 4 mm) were made as shown in Fig.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The maxillary sinus membrane was kept intact during the procedure. The membrane was gently pushed inward and elevated from the floor, lateral wall, and medial wall of the maxillary sinus, and a compartment for graft materials was obtained 1,30 . The hydroxyapatite ceramic particles (diameter 400-1000 mm; Beijing YHJ Science and Trade Co., Beijing, China) were mixed with the blood collected from the auricular vein of each rabbit, packed into the compartment, and slightly compressed (Fig.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Insufficient bone volume and bone quality have been regarded as common limitations for inserting dental implants in the posterior maxilla 1,7 . The most commonly used technique to reconstruct the posterior region of the maxilla is augmentation of the maxillary sinus floor, a technique introduced by BOYNE & JAMES and modified by TATUM and by WOOD & MOORE, in which different osteoconductive materials (bone substitutes) were placed between the host bone and the sinus membrane to allow the insertion of dental implants 4,33,36 .…”
mentioning
confidence: 99%